(untitled) (Veterinary Science, 2017)
Feed efficiency for males and females of two three-way experimental hybrids of free range chickens (Campero Casilda y Campero Pergamino) and in Campero INTA as reference genotype, was calculated in five consecutive weekly periods between 42 and 77 days of age as well as in the overall period. No significant difference among groups in efficiency and related variables were evident in each of the periods, in both sexes. Males were heavier, had higher average daily feed intake, higher average daily weight gain and showed higher feed efficiency and lower conversion ratio than females. The behavior of the two variables ***feed intake and body weight gain*** determining feed efficiency shows that at the end of the fourth of the five periods (63-70 days old), males have already reached the target slaughter weight of 2500 g but not the minimum age (70 days) required by the production protocol, a situation not evident in females. This fact determines that males must be slaughtered at least one week after with a higher body weight (3000 g). Going from 4th to 5th period (70-77 days) increases feed intake and decreases body weight gain, resulting in a decreased feed efficiency, or its equivalent, a deterioration of the feed conversion ratio. In terms of these traits the three genetic groups show equivalent behaviors with conversion values ( 3 kg of feed per kg weight gain) higher than those usually reported for the intensive production model. This situation must be taken into account when poultry meat production takes place under more or less extensive systems that emphasize the preservation of animal welfare